The Effectiveness of Video Vlog Media to Improve Communication and Emotional Skills of Children with ADHD: A Case Study at Elementary School in Surabaya - Zahro, Dike Annisa Ramadina Az; Pinastika , Cahya Nastiti; Farah, Dhea Nailul; Suandi , Ristie (Studies in Learning and Teaching, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) affects the development of communication and emotion management in children, which impacts their ability to interact in the school environment. This study aims to explore the use of video vlog media as a creative approach in helping two learners, Subject S and Subject A, at SDN Ketintang II Surabaya, who have been diagnosed with ADHD, with different characteristics. The research method includes direct observation, video analysis, and interviews with teachers. So based on the research methods, the results of this study show that the use of video vlog media significantly improves the communication and emotional skills of subject S compared to subject A, who is more closed in expression. Therefore, this video vlog media provides a platform that allows them to express themselves more freely, so that they can improve their communication skills and emotional management through an interpersonal approach. However, the importance of assistance by parents and teachers during the implementation is that it can provide the necessary direction to help children overcome the various challenges faced.